2014
DOI: 10.1371/journal.pone.0094754
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Changes in Water Intake on Mood of High and Low Drinkers

Abstract: ObjectiveTo evaluate the effects of a change in water intake on mood and sensation in 22 habitual high-volume (HIGH; 2-4 L/d) and 30 low-volume (LOW; <1.2 L/d) drinkers who were asked to respectively decrease and increase their daily water intake.MethodDuring baseline HIGH consumed 2.5 L and LOW 1 L of water/day. During 3 controlled intervention days HIGH's water intake was restricted to 1 L/day whereas LOW's was increased to 2.5 L water/day. Several mood scales (Bond & Lader Visual Analog Scale (VAS), Profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 24 publications
(28 reference statements)
2
46
1
3
Order By: Relevance
“…Increased water intake may result in decreased sleep during the day; which in turn lead to better sleep at night. This finding is supported by previous studies that showed a positive effect of water consumption on alertness (42,65,66).…”
Section: Discussion:-supporting
confidence: 91%
See 1 more Smart Citation
“…Increased water intake may result in decreased sleep during the day; which in turn lead to better sleep at night. This finding is supported by previous studies that showed a positive effect of water consumption on alertness (42,65,66).…”
Section: Discussion:-supporting
confidence: 91%
“…More active adults living in a warm environment have daily water needs of about 6 L (36). Mild dehydration was reported to increase fatigue, decreased activity, and was associated with sleepiness (37)(38)(39)(40)(41)(42).…”
Section: Discussion:-mentioning
confidence: 99%
“…Interestingly, two previous investigations found no influence of water intake on mood state (Edmonds, Crombie, Ballieux, et al, 2013;; these findings might have resulted due to the small bolus (165 mL; Edmonds, Crombie, Ballieux, et al, 2013) and large range of consumed water volumes (125-2500 mL ;, or due to the sensitivity of the Visual Analog Scale used to evaluate mood. One publication to our knowledge investigated habitual TWI followed by controlled TWI manipulation on mood state (Pross et al, 2014). Contrary to our findings, these authors noted HIGH expressed greater Depression than LOW at baseline; however, these results might be influenced by (1) the six day inpatient experience where activities were restricted, and (2) differential impacts of water intake on mood between males and females, as HIGH included only females in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…This conclusion led to a more realistic experimental design in which subtle changes of hydration status were induced. In this study, habitual high-volume ( ≥ 2 L/day) and low-volume (<1.2 L/day) drinkers were asked to respectively decrease (i.e., to 1 L per day) and increase (i.e., to 2.5 L per day) their daily water intake during 3 controlled intervention days [15] . The effects of these changes in habitual water intake were measured on mood and sensations at several time points during the day.…”
Section: Mild Dehydration and Cognition In Adultsmentioning
confidence: 99%